EEVEE: the Empathy-Enhancing Virtual Evolving Environment - Jackson, Philip L.; Michon, Pierre-Emmanuel; Geslin, Erik; Carignan, Maxime; Beaudoin, Danny (Frontiers in Human Neuroscience, 2015)
Empathy is a multifaceted emotional and mental faculty that is often found to be affected in a great number of psychopathologies, including schizophrenia, yet it remains very difficult to measure in an ecological context. The challenge stems partly from the complexity and fluidity of this social process, but also from its covert nature. A powerful tool to enhance experimental control over such dynamic social interactions is the use of avatars in virtual reality (VR), and one way to collect information about an individual in an interaction is through the analysis of his or her neurophysiological and behavioural responses. We have developed a unique platform, the Empathy-Enhancing Virtual Evolving Environment (EEVEE), which is built around three main components: 1) different avatars capable of expressing feelings and emotions at various levels based on the Facial Action Coding System (FACS); 2) systems for measuring the physiological responses of the observer (heart and respiration rate, skin conductance, gaze and eye movements, facial expression); and 3) a multimodal interface linking the avatar’s behaviour to the observer’s neurophysiological response. In this article, we provide a detailed description of the components of this innovative platform and validation data from the first phases of development. Our data show that healthy adults can discriminate different negative emotions, including pain, expressed by avatars at varying intensities. We also provide evidence that masking part of an avatar’s face (top or bottom half) does not prevent the detection of different levels of pain. Overall, this innovative and flexible platform provides a unique tool to study and even modulate empathy in a comprehensive and ecological manner in number of populations suffering from neurological or psychiatric disorders.